(3cJGH GdEeGe jMji Hf MeRI Edi ef hba Ydjg ef GdbHGFd hcJH CNQi dgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3SdGe Gddg Ydjce , aEfG fMeO Gddg Edjce , hfCeQce HJbhi Gddg JYGdi hEbGe GdUdGI hEHJOGA GdRcGI aEfgeG YehOGf ef CYeOI GdPjf s
(3BNQgG (B:s
(3hdcf QjeG JQGceJ GdCTZGd Je CdaGX GdeDjO HGddg CejQ GdeDefjf jMji Hf MeRI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B824s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3GdJhMjO hGdedd hGdfMds